Fermentasi Kulit Nanas Menjadi Bioetanol Menggunakan Zymomonas Mobilis Dengan Variasi Pemekatan Medium Dan Waktu Fermentasi - Adli Satria Sandika; Sri Rezeki Muria; Silvia Reni Yenti (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2017)
The high dependence of fuel resource such as oil, coal, and gas will influence the depletion of fossil resources (oil, natural gas, and coal). Therefore, it is important to study conversion of pineapple peel to bioethanol as renewable energy to overcome dependence on fossil fuels. This research was conducted the fermentation of pineapple peel with concentrated medium variation to obtain high concentration of bioethanol. This work is aimed to study of bioethanol production from pineapple peel with concentrated medium variation with Zymomonas mobilis to increasing the concentration of the sugar inside the medium to obtain maximum conditions on producing bioethanol. Fermentation was conducted in 2 Liter fermentor with variations of fermentation time from 12 ; 24 ; 36 ; 48 ; 60 ; 72 until 84 hours respectively and concentratedmedium variation from 15% ; 20% ; 25% until 30%. respectively. The concentration of bioethanol was increased by increasing of concentrated medium variation. Maximum conditions of bioethanol production from pineapple peel were shown having 30%concentrated medium variation, and fermentation hours 60th about 8,79 % v/v.Keywords: bioethanol, concentrated, pineapple peel, Zymomonas Mobilis